A biomass-derived carbon composite transition metal chalcogenide solid solution electrode material
By loading transition metal chalcogenide nanoparticles with particle size less than 10 nm on the biomass-derived carbon framework, a solid solution structure is formed, and the problems of low specific capacity and poor cycle stability in sodium ion batteries are solved, and high specific capacity, good cycle stability and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202211256223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-13
AI Technical Summary
The existing monometal sulfide electrode materials have problems such as low specific capacity, poor cycle stability and rate performance in sodium ion batteries, and the uneven aggregation and distribution of nanoparticles lead to structural damage and short cycle life.
A biomass-derived carbon composite transition metal chalcogenide solid solution is used as the electrode material, and a more stable solid solution structure is formed by uniformly loading transition metal chalcogenide nanoparticles with particle size less than 10 nm on the three-dimensional network carbon framework.
The specific capacity and cyclic stability of the electrode material are significantly improved, the electron conductivity and ion transport capability are enhanced, and the rate performance and structural stability are improved.
Smart Images

Figure HDA0003889694080000011 
Figure HDA0003889694080000012 
Figure HDA0003889694080000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery materials, and in particular relates to an electrode material of a biomass-derived carbon composite transition metal sulfide solid solution. Background Art
[0002] With the rapid development of science and technology and industry, energy and environmental crises have become one of the biggest challenges facing human society in the 21st century. In order to meet the growing energy demand and increasingly stringent environmental regulations, renewable energy sources including wind, sunlight, waves and tides are gradually becoming potential alternatives to fossil fuels. However, these environmentally friendly energy sources cannot be obtained in time and are largely affected by climate, season and region. In this context, higher requirements are placed on energy storage devices, among which electrochemical energy storage systems have attracted much attention due to their advantages such as short construction period, adjustable capacity and flexible use. At present, the combination of energy conversion and electrochemical energy storage technology is considered to be an ideal strategy for the effective utilization of these renewable energy sources, and the stored electrical energy can be used at any time. Since Sony commercialized lithium-ion batteries in 1991, lithium-ion batteries have been widely used in portable devices and electric vehicles due to their advantages such as long cycle life, high energy density and good rate performance, and dominate the world electrochemical power supply market. However, lithium batteries are costly due to the scarcity and uneven distribution of lithium resources, and cannot fully meet the needs of large-scale power generation. As the most competitive and promising alternative to lithium-ion batteries, sodium-ion batteries have obvious advantages in cost, resources, and safety, and can achieve large-scale and low-cost application of renewable energy. In addition, since sodium and lithium belong to the same main group on the periodic table, they have similar chemical properties and parallel working principles. However, compared with lithium-ion battery systems, sodium has a larger ionic radius (1.02 Å for Na + vs 0.76 Å for Li + ), and the reduction potential (300 mV) is higher than that of lithium, which puts higher requirements on the electrode materials used in sodium-ion batteries. At present, some materials successfully used in lithium-ion batteries have been proven to be unsuitable for use in sodium-ion batteries due to poor sodiumation / depreciation kinetics. In addition, the larger radius of sodium metal ions usually leads to instability of the solid electrolyte interphase layer and collapse of the crystal structure of the main material, resulting in decreased electrochemical performance. In this case, it is very necessary to explore suitable negative electrode materials with high capacity and cycle stability.
[0003] Generally, the electrochemical reaction mechanism of negative electrode materials can be divided into three categories: intercalation, conversion, and alloying. Intercalation negative electrode materials have superior cycle life, but the specific capacity is relatively low. As for conversion and alloy negative electrodes, although the theoretical capacity is high, the cycle stability and safety issues are of great concern. For this reason, finding suitable negative electrode materials has become the focus of researchers. So far, many materials have been explored as negative electrodes for sodium-ion batteries, such as carbon materials, alloy materials, organic materials, and metal sulfides / oxides / phosphides. Transition metal sulfides and selenides (denoted as MX, M=Fe, Co, Ni, Cu, Zn, Mn, etc., X=S, Se) show strong competitiveness due to their superior advantages. First, the morphological controllability of MX is conducive to improving its electrochemical performance. And from the perspective of a single conversion reaction mechanism, MX not only provides high specific capacity, but also shows good cycle life by limiting the discharge depth to a suitable position. In addition, compared with the corresponding metal oxides, MX has better reaction kinetics in the conversion reaction because the MS / Se bond is weaker than the MO band and has higher conductivity. Despite this, MX still faces some disadvantages as anode materials for sodium-ion batteries, including large volume changes during conversion reactions, low electronic conductivity of some MX, and dissolution shuttling of polysulfides or polyselenides. In order to solve the above dilemma, introducing one or more transition metal cations into MX to form a solid solution of MX is a widely adopted strategy to make up for the lack of single metal sulfides or selenides. The preparation of this solid solution can significantly change its inherent properties, and can produce richer redox reactions and better conductivity compared with the original parent MX. At the same time, the synergistic effect induced by the multi-element properties helps to further significantly improve the sodium storage capacity. In addition, in sharp contrast to the heterogeneous structure of mixed bimetallic sulfides, solid solutions with single-phase characteristics are inherently more stable because the interaction within the solid solution is stronger than the hybridization. In addition to the above strategies, the addition of carbon matrices of various geometries to the MX anode can cause structural changes and greatly improve the ion transport rate, which is recognized as another feasible method. Some examples of this configuration are loading MX particles onto various carbon matrices (graphene, carbon nano / microtubes, carbon fibers and other carbon structures) or tightly wrapping the MX surface with core-shell carbon. Biomass materials have significant advantages such as being renewable, cost-effective, and complex in structure, and are excellent precursor materials for the preparation of complex carbon skeletons. In addition, since the raw materials are sustainable resources, no complex methods are required to achieve design and preparation, which is itself a low-cost method. Natural herbaceous plant-derived carbon skeletons have excellent electrical conductivity and a tubular structure with randomly arranged nanopores interconnected, which is conducive to efficient charge storage and rapid ion transport.For example, the invention patent CN112599770A discloses a negative electrode material for lithium / sodium ion batteries and a preparation method thereof, wherein the negative electrode material is based on a biomass carbon material, and the base is loaded with carbon-coated sulfide particles with a transition metal sulfide as the core. However, the above-mentioned transition metal sulfide is a single metal sulfide of nickel sulfide, cobalt sulfide, vanadium sulfide, molybdenum sulfide or manganese sulfide, with low specific capacity, poor cycle stability and rate performance. The invention patent CN114864291A discloses a method for preparing a NiCo2S4 / enzymatic lignin carbon electrode material for supercapacitors, and a NiCo2S4 / enzymatic lignin carbon composite material prepared by a solvothermal method. However, the irregularly aggregated NiCo2S4 nanoparticles are randomly arranged and distributed on the surface of the carbon matrix, and structural destruction, crushing and agglomeration occur during the charge and discharge process, thereby affecting the specific capacity and cycle life. Therefore, there are still huge challenges in developing a biomass-derived carbon-modified composite multimetallic sulfide solid solution structure to achieve high electrochemical performance. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an electrode material of a biomass-derived carbon composite transition metal sulfide solid solution to solve the problems of low specific capacity, poor cycle stability and rate performance, and aggregation and uneven distribution of nanoparticles in existing single metal sulfide electrode materials, which lead to structural destruction, crushing and agglomeration during the charge and discharge process.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: an electrode material of a biomass-derived carbon composite transition metal sulfide solid solution, comprising a biomass-derived carbon skeleton with a three-dimensional network hollow tubular structure and transition metal sulfide solid solution nanoparticles loaded on the surface of the carbon skeleton, wherein the nanoparticles are evenly distributed and dense, and the particle size of the nanoparticles is less than 10 nm; the electrode material has a chemical composition represented by ABX@BDC, wherein A and B are independently selected from one of the transition metal elements Fe, Co, Ni, Cu, Mn, Zn and Sn, and A and B are different, X is a non-metallic element S or Se, and BDC is a biomass-derived carbon skeleton. In this way, the three-dimensional network carbon skeleton can have a high specific surface area and mesoporous structure, which can effectively increase the contact area between the electrode and the electrolyte, thereby providing abundant ion insertion sites and transmission channels for the transmission of sodium ions; and the ultra-small solid solution sulfide nanoparticles with a particle size of less than 10 nm are evenly and densely anchored on the surface of the three-dimensional carbon skeleton, which can effectively inhibit the structural destruction, crushing and agglomeration during the repeated de-sodiumization process during the charging and discharging process, thereby showing a high specific capacity and good cycle life.
[0006] Preferably, the BDC is a hollow carbon tube skeleton derived from biomass rush or a hollow carbon tube skeleton derived from kapok fiber.
[0007] Another object of the present invention is to provide a method for preparing an electrode material of a biomass-derived carbon composite transition metal chalcogenide solid solution, comprising the following steps:
[0008] 1) The biomass was ultrasonically treated in deionized water, washed and dried;
[0009] 2) Soaking the biomass obtained in step 1) in a mixed solution containing transition metal salt A, transition metal salt B and glycine for 12 to 24 hours, then taking it out and placing it in a vacuum oven for drying; wherein the cobalt salt can be selected from one or more of cobalt nitrate, cobalt acetate and cobalt chloride; and the nickel salt can be selected from one or more of nickel nitrate, nickel acetate and nickel chloride.
[0010] 3) The biomass containing ions A and B prepared in step 2) is heated to 300-450 o C for 5 to 60 min, and then naturally cool down after the reaction to prepare a three-dimensional network A / B / BDC composite material;
[0011] 4) The A / B / BDC composite material and the sulfur source / selenium source prepared in step 3) are placed in two porcelain boats respectively and wrapped with a piece of tin foil, and then subjected to sulfurization or selenization treatment in a protective atmosphere. After the reaction is completed, the temperature is naturally lowered to obtain the electrode material.
[0012] In this way, through the special effect of glycine in the mixed solution of transition metal ions and with the help of effective high-temperature combustion treatment, the loading of ultra-small sulfide solid solution nanoparticles on the three-dimensional interconnected tubular carbon skeleton is effectively achieved. Compared with other reported biomass-derived carbon-loaded nanoparticles, these nanoparticles have more uniform and dense structural characteristics.
[0013] Preferably, the biomass is rush or kapok fiber.
[0014] Preferably, the sulfur source is sublimated sulfur and / or thiourea, and the selenium source is selenium powder.
[0015] Preferably, in step 2), the molar ratio of the transition metal salt A to the transition metal salt B is 2:1-1:2; and the concentration of glycine in the mixed solution is 5-20 mmol.
[0016] Preferably, the mass ratio of the A / B / BDC composite material to the sulfur source / selenium source is 1:1 to 1:20.
[0017] Preferably, the high temperature sulfurization / selenization treatment is performed at 1 to 10 o C / min and then heat up to 350 ~ 800 ℃ and keep it at that temperature for 0.5 ~ 5 h.
[0018] Preferably, the protective atmosphere is argon or nitrogen; and the drying temperature is 80-100°C.
[0019] Another object of the present invention is to provide the use of the above-mentioned novel metal sulfide solid solution electrode material or the novel metal sulfide solid solution electrode material prepared by the above-mentioned method in sodium ion batteries.
[0020] The electrode material of biomass-derived carbon composite transition metal sulfide solid solution provided by the present invention has a biomass-derived carbon skeleton with a three-dimensional network structure, which not only realizes the high mass loading of ultra-small solid solution nanoparticles, but also enhances the electronic conductivity of these nanoparticles, and significantly promotes electron transmission. At the same time, the three-dimensional network carbon skeleton can have a high specific surface area and a mesoporous structure, which can effectively increase the contact area between the electrode and the electrolyte, thereby providing abundant ion insertion sites and transmission channels for the transmission of sodium ions. More importantly, the ultra-small solid solution sulfide nanoparticles are uniformly and densely anchored on the inner and outer wall surfaces of the three-dimensional carbon skeleton, and can effectively inhibit the structural destruction, crushing and agglomeration in the repeated de-sodium process during the charge and discharge process, thereby showing a high specific capacity and good cycle life. Compared with the electrode material of single metal sulfide composite biomass carbon, the present invention exhibits better reversible specific capacity, more excellent cycle life and rate performance, and better sodium ion diffusion coefficient.
[0021] The present invention uses biomass as raw material, and prepares and synthesizes a three-dimensional network hollow tubular carbon skeleton composite transition metal sulfide solid solution through metal ion adsorption, combustion treatment and sulfidation / selenization treatment. Among them, through the special effect of glycine in the metal ion mixed solution, and with the help of effective combustion treatment, the uniform loading of ultra-small sulfide solid solution nanoparticles on the three-dimensional interconnected tubular carbon skeleton is effectively achieved. Compared with other reported biomass-derived carbon-loaded nanoparticles, the nanoparticles have more uniform and smaller particle size structural characteristics. The electrode material prepared by the present invention has better specific capacity, better cycle stability and rate performance. And it has attractive reversible capacity, ultra-long cycle life and good structural stability at ultra-high rate. Compared with metal sulfide solid solutions synthesized by other methods, the present invention has abundant raw material resources, low cost, simple preparation process, less time consumption, and extremely easy reaction conditions. It can be mass-produced and is convenient for commercial application.
[0022] The present invention uses green, economical and sustainable biomass waste as carbon precursor. The raw materials are widely derived from natural plants and are low in cost. The application in sodium ion batteries can significantly reduce the preparation cost. It not only broadens the utilization direction of nitrogen-containing biomass waste, but also alleviates the pressure on the environment caused by a large amount of nitrogen-containing biomass waste. It is in line with the long-term goals of green environmental protection and sustainable development, and realizes the energy storage development concept of "turning waste into treasure". It shows great application prospects in sodium ion batteries. It lays a foundation for the design and preparation of green and low-cost solid solution sulfide / carbon composite materials extracted from renewable biomass resources in the future, promotes its commercial application prospects in environmentally friendly energy storage systems, and inspires new ways to design green and environmentally friendly electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the biomass rush after carbonization in Example 1.
[0024] Figure 2 Scanning electron microscope and transmission electron microscope images of NiCo2S4 / BDC prepared in Example 1.
[0025] Figure 3 This is the scanning electron microscope image of NiCo2S4 / BDC prepared in comparative example 3.
[0026] Figure 4 X-ray diffraction patterns of NiCo2S4 / BDC prepared in Example 1 and the comparative examples NiS / BDC and CoS / BDC composite materials.
[0027] Figure 5 Thermogravimetric analysis diagrams of NiCo2S4 / BDC prepared in Example 1 and comparative examples NiS / BDC and CoS / BDC composite materials.
[0028] Figure 6 X-ray photoelectron spectra of the NiCo2S4 / BDC prepared in Example 1 and the comparative examples NiS / BDC and CoS / BDC composite materials.
[0029] Figure 7 CV curves of NiCo2S4 / BDC prepared in Example 1 and the comparative examples NiS / BDC and CoS / BDC composite materials at different scan rates; a is NiCo2S4 / BDC, b is NiS / BDC, and c is CoS / BDC.
[0030] Figure 8 Comparison diagram of initial charge and discharge (a) and cycle stability (b) of NiCo2S4 / BDC prepared in Example 1 and comparative examples NiS / BDC and CoS / BDC composite materials.
[0031] Fig. 9This is a comparison chart of the rate performance of the NiCo2S4 / BDC prepared in Example 1 and the comparative examples NiS / BDC and CoS / BDC composite materials.
[0032] Fig.10 The NiCo2S4 / BDC composite material prepared in Example 1 was prepared at 20.0 A g -1 Cycling stability plot at different current densities. DETAILED DESCRIPTION
[0033] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, but the embodiments are not intended to limit the present invention. The experimental methods without specific conditions in the preferred embodiments are usually carried out under conventional conditions or under conditions recommended by the reagent manufacturer.
[0034] 1. A method for preparing an electrode material of a biomass-derived carbon composite transition metal chalcogenide solid solution Embodiment 1:
[0035] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0036] 2) Dissolve 4.5 mmol Ni(NO3)2·6H2O, 4.5 mmol Co(NO3)2·6H2O and 10 mmol glycine in 50 ml of deionized water and stir evenly for 30 min to obtain a mixed solution. Then, 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then, it was taken out and dried in an oven for 60 o C drying treatment.
[0037] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0038] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / BDC-derived carbon (NiCo2S4 / BDC) composite material. Embodiment 2:
[0039] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0040] 2) Dissolve 4.5 mmol Ni(CH3COO)2·4H2O, 4.5 mmol Co(CH3COO)2·4H2O and 10 mmol glycine in 50 ml of deionized water and stir evenly for 30 min to obtain a mixed solution. Then, 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then, it was taken out and dried in an oven for 60 o C drying treatment.
[0041] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0042] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 3:
[0043] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0044] 2) 4.5 mmol NiCl2·4H2O, 4.5 mmol CoCl2·4H2O and 10 mmol glycine were dissolved in 50 ml of deionized water and stirred evenly for 30 min to obtain a mixed solution. Then 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then it was taken out and dried in an oven for 60 o C drying treatment.
[0045] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0046] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 4:
[0047] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0048] 2) Dissolve 4.5 mmol Ni(NO3)2·6H2O, 4.5 mmol Co(CH3COO)2·4H2O and 10 mmol glycine in 50 ml of deionized water and stir evenly for 30 min to obtain a mixed solution. Then, 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then, it was taken out and dried in an oven for 60 o C drying treatment.
[0049] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0050] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 5:
[0051] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0052] 2) Dissolve 4.5 mmol Ni(CH3COO)2·4H2O, 4.5 mmol Co(NO3)2·6H2O and 10 mmol glycine in 50 ml of deionized water and stir evenly for 30 min to obtain a mixed solution. Then, 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then, it was taken out and dried in an oven for 60 o C drying treatment.
[0053] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0054] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 6:
[0055] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0056] 2) 4.5 mmol NiCl2·4H2O, 4.5 mmol Co(CH3COO)2·4H2O and 10 mmol glycine were dissolved in 50 ml of deionized water and stirred evenly for 30 min to obtain a mixed solution. Then 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then it was taken out and dried in an oven for 60 o C drying treatment.
[0057] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0058] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 7:
[0059] 1) 10 g of biomass rush was soaked in 200 ml of deionized water and ultrasonically treated for 1 h, then soaked at room temperature for 24 h, and dried in an oven for 60 o C drying treatment.
[0060] 2) Dissolve 4.5 mmol Ni(CH3COO)2·4H2O, 4.5 mmol CoCl2·4H2O and 10 mmol glycine in 50 ml of deionized water and stir evenly for 30 min to obtain a mixed solution. Then, 3 g of rush obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then, it was taken out and dried in an oven for 60 o C drying treatment.
[0061] 3) Place the rush loaded with cobalt ions and nickel ions in step 2) into a 400 o C was burned in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / rush composite.
[0062] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / rush-derived carbon composite material. Embodiment 8:
[0063] 1) 10 g of biomass kapok fiber was soaked in 200 ml of 2 M sodium hydroxide solution and then heated at 60 o C water bath for 10 h to remove paraffin and ash on the surface of kapok fiber, and then rinsed with deionized water 3-5 times and placed in a vacuum oven at 60 ° C overnight.
[0064] 2) 4.5 mmol Ni(NO3)2·6H2O, 4.5 mmol Co(NO3)2·6H2O and 10 mmol glycine were dissolved in 50 ml of deionized water and stirred evenly for 30 min to obtain a mixed solution. Then 3 g of biomass kapok fiber obtained in step 1) was directly immersed in the mixed solution and allowed to stand for 12 h. Then it was taken out and dried in an oven for 60 o C drying treatment.
[0065] 3) Place the kapok fibers loaded with cobalt ions and nickel ions in step 2) at 400 o C in a muffle furnace for 10 min, then quickly taken out and cooled naturally to obtain a Ni / Co / kapok fiber composite.
[0066] 4) 0.2 g of the Ni / Co / rush composite prepared in step 3) and 1.0 g of sublimed sulfur were placed in two porcelain boats, wrapped with a piece of tin foil, and then directly transferred into a tubular furnace filled with argon gas at 2 o C / min heating rate to 600 o C and maintained for 2 h. After the reaction was completed, the temperature was naturally lowered to prepare the NiCo2S4 / kapok fiber-derived carbon composite material.
[0067] Comparative Example 1:
[0068] In step 2), Ni(NO3)2·6H2O was not added, and the other steps were the same as in Example 1 to prepare a NiS / juncus briar-derived carbon (NiS / BDC) composite material.
[0069] Comparative Example 2:
[0070] In step 2), Co(NO3)2·6H2O was not added, and the other steps were the same as in Example 1 to prepare a CoS / BDC-derived carbon (CoS / BDC) composite material.
[0071] Comparative Example 3:
[0072] In step 2), no glycine was added and no combustion treatment was performed. The other steps were the same as in Example 1 to prepare a NiCo2S4 / BDC-derived carbon (NiCo2S4 / BDC) composite material.
[0073] 2. Performance Testing
[0074] 1. The carbon skeleton and NiCo2S4 / BDC composite material prepared by directly annealing the cleaned biomass rush in Example 1 were observed under a scanning electron microscope and a transmission electron microscope, respectively. The results are as follows: Figure 1 and 2 shown.
[0075] Depend on Figure 1 a and Figure 1 b It can be seen that the carbon material derived from biomass rush shows a beautiful three-dimensional network structure, a smooth surface, and a carbon skeleton with obvious hollowness, high specific surface area and mesoporous structure. Figure 2 a and Figure 2b It can be seen that a large number of uniform NiCo2S4 nanoparticles with a particle size of about 5-10 nm are anchored on the inner and outer walls of the biomass-derived hollow carbon skeleton with a three-dimensional network structure, and the carbon skeleton still maintains an obvious hollow structure. Figure 2 The TEM of c confirmed that the ultra-small NiCo2S4 nanoparticles are uniformly and densely anchored on the surface of the three-dimensional carbon skeleton. Therefore, during the charge and discharge process, the structural damage, crushing and agglomeration during the repeated sodium removal process can be effectively suppressed, thus showing a high specific capacity and good cycle life. Figure 2 From the HRTEM of d, it can be seen that two lattice fringes with interplanar spacing of 0.236 nm and 0.332 nm are displayed in two regions of about 10 nm, which correspond to the (400) and (220) crystal planes of NiCo2S4, respectively.
[0076] Figure 3 This is a morphology of the NiCo2S4 / BDC composite material prepared in Example 3 under a scanning electron microscope. It can be seen that the particle size of the NiCo2S4 nanoparticles in the composite material prepared by the conventional method (without adding glycine and without combustion treatment) is significantly larger than that of the present invention. At the same time, a large number of NiCo2S4 nanoparticles are randomly and sparsely distributed on the carbon skeleton, which is prone to structural damage and crushing during repeated charging.
[0077] 2. X-ray diffraction, X-ray photoelectron spectroscopy and thermogravimetric analysis were performed on the NiCo2S4 / BDC prepared in Example 1, the NiS / BDC prepared in Comparative Example 1 and the CoS / BDC composite materials prepared in Comparative Example 2. The results are as follows: Figures 4 to 6 shown.
[0078] from Figure 4 From the X-ray diffraction patterns, we can see that all the diffraction peaks of the three composite materials correspond to the cubic phases of NiCo2S4, NiS and CoS. However, no diffraction peaks related to the carbon skeleton were found, proving that the carbon skeleton has an amorphous crystal structure. Figure 5 The thermogravimetric analysis shows that from room temperature to 200 o C shows a mass loss, which is mainly caused by the volatilization of the attached water inside the sample. o C to 700 o The mass loss of C is due to the reaction of S and C with oxygen in the air to produce SO2 and CO2 gases. o The stability of C is due to the production of Co3O4 and NiO. Through analysis, the mass percentages of NiCo2S4, NiS and CoS in NiCo2S4 / BDC, NiS / BDC and CoS / BDC composites are 73.6%, 51.7% and 53.5% respectively. Figure 6 It can be seen from the X-ray photoelectron spectrum that some expected elements such as Ni, Co, Se and C were monitored in the three composite materials of NiCo2S4 / BDC, NiS / BDC and CoS / BDC. The above results show that compared with the single metal sulfide / BDC material, the bimetallic sulfide solid solution achieves a higher loading on BDC.
[0079] 3. Take the NiCo2S4 / BDC prepared in Example 1, the NiS / BDC prepared in Comparative Example 1 and the CoS / BDC prepared in Comparative Example 2 as the negative electrode materials, mix them with Ketjen black and CMC binder in a mass percentage of 60:30:10, add an appropriate amount of deionized water, grind them into a paste in an agate mortar, apply them on a copper foil with a diameter of 13 mm, and then vacuum dry the copper foil at 80°C for 12 h to obtain the negative electrode sheet of the sodium ion battery, and then transfer it to a glove box filled with argon gas for assembly of button batteries. The button battery model is CR2032, the metal sodium sheet is used as the counter electrode, the diaphragm is glass fiber, and the electrolyte is 1 mol / L NaCF3SO3 solution (the solvent is diethylene glycol dimethyl ether solution). The assembled battery was subjected to cyclic voltammetry (CV) tests at different scan rates of 0.2 ~ 2.0 mV / s (electrochemical workstation CHI-660E, voltage range 0.01 ~ 3.0 V, the same below). The results are as follows: Figure 7 shown.
[0080] As can be seen from the figure, the peak current of the CV curves of the three composite materials gradually increases with the increase of the scan rate. And the oxidation peak and the reduction peak slightly shift in opposite directions with the increase of the scan rate, proving the extremely small polarizability of the three materials. In addition, as the scan rate increases, the CV curve shape of the three materials remains good, and the existence of the redox peak can be clearly monitored, indicating that the NiCo2S4 / BDC, NiS / BDC and CoS / BDC composite materials have good rate performance.
[0081] 4. The three composite materials of NiCo2S4 / BDC, NiS / BDC and CoS / BDC prepared in Example 1 were assembled into CR2032 button batteries, and then the batteries were heated at 1.0 A g -1 The cycle stability test was carried out at a current density of Figure 8 shown.
[0082] from Figure 8 As can be seen from a, the initial charge and discharge capacities of the NiCo2S4 / BDC composite material prepared by the present invention are 889.8 mAh g -1 and 714.5 mAh g -1The corresponding initial coulombic efficiency is 80.3%. The initial charge and discharge capacities of the comparative examples NiS / BDC and CoS / BDC are 692.5 / 543.1 mAh g -1 and 562.8 / 424.9 mAh g -1 , and the corresponding initial Coulomb efficiencies are 78.4% and 75.5% respectively. Figure 7 As can be seen in b, after 60 cycles, the discharge capacity of the NiCo2S4 / BDC electrode is still 614.0 mAh g -1 The capacity retention is 85.4% of the second cycle discharge capacity, which is much better than the 455.5 mAh g of NiS / BDC in the comparative example 1. -1 and 374.6 mAh g of CoS / BDC in comparative example 2 -1 , indicating that the solid solution NiCo2S4 / BDC composite material has better cycling stability and specific capacity than the single metal NiS / BDC and CoS / BDC composite materials.
[0083] 5. The NiCo2S4 / BDC, NiS / BDC and CoS / BDC composite materials prepared in Example 1 were assembled into CR2032 button batteries, and then the batteries were heated to 0.2 ~ 20.0 A g -1 The discharge specific capacity was measured under the current density condition (on Land2001A test system, the voltage range was 0.01 ~ 3.0 V, the same below), and the results are as follows Fig. 9 shown.
[0084] It can be seen from the figure that when the current density is 0.2 A g -1 , 0.4 A g -1 , 0.6 A g -1 , 0.8 A g -1 , 1.0 Ag -1 and 1.5 A g -1 When the discharge capacity of NiCo2S4 / BDC electrode is 714.5 mAh g -1 、677.8 mAh g -1 、637.9 mAh g -1 、581.9 mAh g -1 、475.6 mAh g -1 and 376.1 mAh g -1 When the current density changes rapidly to 20.0 A g -1 When the specific capacity is still maintained at 292.4 mAh g -1 Then, when the current density gradually recovered to 0.2 Ag -1When the capacity is restored to 855.9 mAh g -1 However, for NiS / BDC and CoS / BDC electrodes, their capacities are significantly lower than the specific capacity of NiCo2S4 / BDC electrodes at all rates, indicating that the solid solution NiCo2S4 / BDC composite material has superior rate performance compared to the single metal NiS / BDC and CoS / BDC composite materials.
[0085] 6. As above, the NiCo2S4 / BDC electrode material prepared in Example 1 was assembled into a CR2032 button cell, and then the cell was heated at 20.0 A g -1 The cycle stability test was carried out at a current density of Fig.10 shown.
[0086] It can be seen from the figure that the initial discharge capacity of the NiCo2S4 / BDC composite material prepared by the present invention is 474.4 mAh g -1 After 3200 cycles, its discharge capacity is still 231.7 mAh g -1 , which shows that the material still has good structural stability and cycle life at ultra-high rates.
[0087] It should be noted that the electrode materials prepared in Examples 2 to 8 also have good and cycle-stable electrochemical properties, which are not listed here one by one.
[0088] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A biomass-derived carbon composite transition metal chalcogenide solid solution electrode material, characterized in that: The invention comprises a biomass-derived carbon skeleton having a three-dimensional network hollow tubular structure and transition metal sulfide solid solution nanoparticles loaded on the carbon skeleton, wherein the nanoparticles are evenly distributed and densely anchored on the inner wall and outer wall surface of the carbon skeleton, and the particle size of the nanoparticles is less than 10 nm; the electrode material has a chemical composition represented by ABX@BDC, wherein A and B are independently selected from one of the transition metal elements Fe, Co, Ni, Cu, Mn, Zn and Sn, and A and B are different, X is a non-metallic element S or Se, and BDC is a biomass-derived carbon skeleton; The electrode material of the biomass-derived carbon composite transition metal chalcogenide solid solution is prepared by the following method: 1) The biomass was ultrasonically treated in deionized water, washed and dried; 2) soaking the biomass obtained in step 1) in a mixed solution containing transition metal salt A, transition metal salt B and glycine for 12 to 24 hours, then taking it out and placing it in a vacuum oven for drying; 3) The biomass containing ions A and B prepared in step 2) is heated to 300-450 o C for 5 to 60 min, and then naturally cool down after the reaction to prepare a three-dimensional network A / B / BDC composite material; 4) The A / B / BDC composite material and the sulfur source / selenium source prepared in step 3) are placed in two porcelain boats respectively and wrapped with a piece of tin foil, and then subjected to high-temperature sulfurization or selenization treatment in a protective atmosphere. After the reaction is completed, the temperature is naturally lowered to obtain the electrode material.
2. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The BDC is a hollow carbon tube skeleton derived from biomass rush or a hollow carbon tube skeleton derived from kapok fiber.
3. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The biomass is rush or kapok fiber.
4. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The sulfur source is sublimated sulfur and / or thiourea, and the selenium source is selenium powder.
5. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: In step 2), the molar ratio of transition metal salt A to transition metal salt B is 2:1-1:2; and the concentration of glycine in the mixed solution is 5-20 mmol.
6. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The mass ratio of the A / B / BDC composite material to the sulfur source / selenium source is 1:1 to 1:
20.
7. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The high temperature sulfurization / selenization treatment is 1 to 10 o C / min and then heat up to 350 ~ 800 ℃ and keep it at that temperature for 0.5 ~ 5 h.
8. The electrode material of biomass-derived carbon composite transition metal chalcogenide solid solution according to claim 1, characterized in that: The protective atmosphere is argon or nitrogen; the drying temperature is 80-100°C.
9. Use of the electrode material of the biomass-derived carbon composite transition metal sulfide solid solution according to any one of claims 1 to 8 in a sodium ion battery.
Citation Information
Patent Citations
Lithium / sodium ion battery negative electrode material and preparation method thereof
CN112599770A
Preparation method of NiCo2S4 / enzymatic hydrolysis lignin carbon electrode material for supercapacitor
CN114864291A
Novel metal chalcogenide solid solution electrode material and preparation method and application thereof
CN114725353A